The Effects of Integrated Provision Action Observation and Synchronized Electrical Sensory Stimulation for Sit-to-stand in Stroke Patients Function - Young Moon; Jong-duk Choi (Korean Research Society of Physical Therapy, 2020)
Background: Stroke patients experience multiple dysfunctions that include motor and sensory impairments. Therefore, new intervention methods require a gradational approach depending on functional levels of a stroke patient's activity and should include cognition treatment to allow for a patient's active participation in rehabilitation. Objects: This study investigates the effect of integrated revision of electrical sensory stimulation, which stimulates somatosensory and action observation training, which is synchronized cognition intervention method on stroke patients' functions. Methods: Twenty-one stroke patients were randomized into two groups. The two groups underwent twenty minutes of intervention five times a week for three weeks. This study used an electromyogram to evaluate symmetric muscle activation of lower extremities and muscle onset time when performing sit to stand before and after intervention. A weight-bearing ratio was used to evaluate the weight-bearing of the affected side in a sit to standing. To evaluate sit to stand performance ability, this study performed five timed sit to stand tests. Results: The two groups both showed statistically significant improvement in muscle onset time of lower extremity, static balance ability in a standing position, and sit to stand performance after the intervention (p < 0.05). In addition, the action observation and synchronized electrical sensory stimulation group showed significant improvement in symmetric muscle activation of lower extremities and weight-bearing ratio of the affected side (p < 0.05). Conclusion: action observation and synchronized electrical sensory stimulation (AOT with ESS) can have positive effects on a stroke patient's sit to stand performance, and the intervention method that provides integrated AOT with ESS can be used as new nervous system intervention program.